2017
DOI: 10.1099/ijsem.0.001912
|View full text |Cite
|
Sign up to set email alerts
|

Saccharopolyspora spongiae sp. nov., a novel actinomycete isolated from the marine sponge Scopalina ruetzleri (Wiedenmayer, 1977)

Abstract: A novel marine actinomycete, designated strain CMAA 1452T, was isolated from the sponge Scopalina ruetzleri collected from Saint Peter and Saint Paul Archipelago, in Brazil, and subjected to a polyphasic taxonomic investigation. The organism formed a distinct phyletic line in the Saccharopolyspora 16S rRNA gene tree and had chemotaxonomic and morphological properties consistent with its classification in this genus. It was found to be closely related to Saccharopolyspora dendranthemae KLBMP 1305T (99.5% 16S rR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…In recent studies, a variety of new species of actinobacteria from marine sponges were continuously identified by researchers, including Actinokineospora spheciospongiae (Kämpfer et al, 2015), Marmoricola aquaticus (de Menezes et al, 2015), Streptomyces spongiicola (Huang et al, 2016), Saccharopolyspora spongiae (Souza et al, 2017) and Williamsia spongiae (de Menezes et al, 2017), Streptomyces reniochalinae and Streptomyces diacarni (Li et al, 2018). Thus, marine sponges have proven to be a good habitat for novel actinomycete species (Abdelmohsen et al, 2014; Huang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, a variety of new species of actinobacteria from marine sponges were continuously identified by researchers, including Actinokineospora spheciospongiae (Kämpfer et al, 2015), Marmoricola aquaticus (de Menezes et al, 2015), Streptomyces spongiicola (Huang et al, 2016), Saccharopolyspora spongiae (Souza et al, 2017) and Williamsia spongiae (de Menezes et al, 2017), Streptomyces reniochalinae and Streptomyces diacarni (Li et al, 2018). Thus, marine sponges have proven to be a good habitat for novel actinomycete species (Abdelmohsen et al, 2014; Huang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies investigating microbial communities of S. ruetzleri and Scopalina sp. have shown that these sponges host phyla (Actinobacteria, Cyanobacteria, Proteobacteria) with potential for natural products synthesis [ 67 , 68 , 71 , 72 , 73 ]. As the crude extract of S. hapalia exhibited interesting biological activities, isolation studies focusing on actinomycetes and filamentous fungi were carried out.…”
Section: Resultsmentioning
confidence: 99%
“…Genomic DNA extraction, PCR amplification and sequencing methods were performed according to procedures adopted in Souza et al (2017) 34 . The 16S rRNA consensus contigs were obtained using PhredPhrap/ Consed 81 and were aligned by ClustalW against nearest corresponding sequences using EzBioCloud 82 and MEGA 7.0 42 .…”
Section: Methodsmentioning
confidence: 99%
“…Compound classes belonging to the peptides, polyketides, macrolides, quinolones and others represent these bioactivities [28][29][30][31][32] . Accordingly, the isolation and identification of actinomycetes have become a fruitful area of research in recent years that has subsequently led to the identification of novel Actinomycete species that should be exploited to unveil possible biosynthetic pathways and discover new bioactive natural products 12,[33][34][35] . Thus, the rhizosphere bacterial composition of Antarctic hairgrass (Fig.…”
mentioning
confidence: 99%